ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2016å¦ç”Ÿå¯¹è¿žè¯ â€œä¸ç®¡â€ä¸Žâ€œæ— è®ºâ€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Wahyuni, Rati Tri; Thamrin, Lili; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractConjunctions are an important part of Chinese grammar.Conjunction is a kind of function words, its role is to connect two words, phrases and clauses.In conjunction with the word "no matter" and "no matter" for example, the two words in the semantics and usage there is a difference and the same.Therefore, students on the?no matter?and?no matter " prone to error. In order to understand the mastery and difficulty of?no matter?and?no matter?students of the Chinese language majoring in Teachers College of Tanjung Pulai National University, the author used the test method to test the students.Test results showed that students have a better grasp of?no matter?than?no matter?."Regardless of" the correct rate of 73%, and?regardless of " the correct rate of 55%.Analysis of difficulties, the author found that students for "whether" to add "or, with, and" grasp the situation is not good.  Keyword: buguan, conjunctions, the analysis of mastery,wulun